Philosophy of Education in the Digital Age: The Balance between Technology and Humanism - Dwi Pita Reski; Syamsu A Kamaruddin; Abdullah Sinring (DIDAKTIKA, 2024)
This research aims to explore the integration of educational philosophy in the context of the digital age to achieve a balance between the utilisation of technology and humanistic values, focusing on the influence of technology on educational practices and students' learning experiences. Through data collection that included interviews with educators, surveys of students' perceptions of technology in learning, and analyses of educational policies, it was found that while technology can improve access to information and interactivity, there is a risk of neglecting essential humanistic values in education. Results show that a balanced approach between technology and humanism not only increases student motivation and engagement, but also strengthens interpersonal relationships in the teaching and learning process. The findings have deep significance in the context of education, where the application of technology must be accompanied by the cultivation of strong moral and social values. The implications of this study point to the importance of developing holistic educational policies, which not only facilitate technology integration, but also support students' character growth and empathy in acquiring knowledge. As such, this research contributes to the endeavour of creating a more humanised educational environment in the growing digital age, and serves as a reference for educators and policy makers to formulate effective strategies in facing today's educational challenges.